Cost and affordability of healthy diets in Vietnam - Van, Duong T.T.; Herforth, Anna W.; Trinh, Huong T.; Dao, Binh T.T.; Do, Ha T.P.; Talsma, Elise F.; Feskens, Edith J.M. (Cambridge University Press, 2024)
Objectives: To estimate the cost and affordability of healthy diets recommended by the 2016–2020 Vietnamese food-based dietary guidelines (FBDG).